Interfacial control of oxygen vacancy doping and electrical conduction in thin film oxide heterostructures - Boyd W. Veal (Nature Portfolio, 2016)
Oxygen vacancies near the interface in oxide heterostructures can lead to large changes in properties, including metal–insulator transition temperatures or catalytic activity. Here, the authors demonstrate a way to reversibly control the oxygen-vacancy concentration and distribution in oxide heterostructures.